High hypoxia status in pancreatic cancer is associated with multiple hallmarks of an immunosuppressive tumor microenvironment - Sadozai, Hassan; Acharjee, Animesh; Kayani, Hateem Z.; Gruber, Thomas; Gorczynski, Reginald M.; Burke, Bernard (Frontiers in Immunology, 2024)
Pancreatic ductal adenocarcinoma (PDAC), the most common form of pancreatic cancer is a particularly lethal disease, that is often diagnosed late and is refractory to most forms of treatment. Tumour hypoxia is a key hallmark of PDAC and is purported to contribute to multiple facets of disease progression such as treatment resistance, increased invasiveness, metabolic reprogramming, and immunosuppression. We used the Buffa hypoxia gene signature as a hypoxia score to profile transcriptomics datasets from PDAC cases and to identify the major immunological hallmarks of hypoxia in pancreatic cancer. First, we demonstrated that this hypoxia score is associated with increased tumour grade and reduced survival suggesting that this score is correlated to disease progression. Furthermore, we validated the expression of key genes from the hypoxia score in PDAC cell lines in vitro.Subsequently, we compared the immune phenotypes of cases with high versus low hypoxia score expression (Hypoxia HI vs. Hypoxia LOW ) to show that high hypoxia is associated with reduced levels of T cells, NK cells and dendritic cells (DC), including the crucial cDC1 subset.Concomitantly, immune-related gene expression profiling revealed that, compared to Hypoxia LOW tumours mRNA levels for multiple immunosuppressive molecules were notably elevated in Hypoxia HI cases. These included checkpoint molecules such as CD276, the "don'teat-me" signal CD47, four members of the Galectin family (Galectin-1, Galectin-3, Galectin-4, Galectin-9) and finally, two important immunoregulatory enzymes, CD73 (NT5E) and cyclooxygenase-2 (COX-2). Using an innovative Random Forest machine learning approach for variable selection, we identified LGASL3 (Galectin-3) as the top gene associated with high hypoxia status and demonstrated in hypoxic PDAC cell lines. In summary, we demonstrated novel associations between hypoxia and multiple immunosuppressive mediators in PDAC, highlighting avenues for improving PDAC immunotherapy by targeting these immune molecules in combination with hypoxia-targeted drugs.